Theorizing community care : from disciplinary power to governmentality to personal care - Powell, Jason L., 1971- (Social Perspectives in the 21st Century (Series Editor: Jason L. Powell, Associate Dean of Faculty,, 2013)
As we enter 2014, an accelerating interest in abuse has arisen due to the implementation of community care policies relying upon informal care and a relentless political campaign to legitimize an enforced obligation to care. The use of care management technologies that focus on assessment and inspection, can, in this policy climate, become a means of surveillance and enforcement of informal caring. It is argued that Michel Foucault offers a set of strategies (Foucault 1977: 205) for understanding how the discourses on community care construct older people's experiences and their identities, as.